Analisa Desain Rangka Mesin Rotary Dryer untuk Pengeringan Maggot Menggunakan Metode Finite Element Analysis - Ahmad Rifqi Shulkhan; Ikhwan Taufik; Sigit Mujiarto; Tri Retno Setiyawati; Arif Rahman Saleh (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Organic waste management is an important issue in addressing environmental problems. One potential solution is bioconversion technology using Black Soldier Fly (BSF) maggots that can break down organic waste and produce larvae with economic value as animal feed. To increase the selling value and extend the shelf life, BSF larvae need to be dried using tools such as rotary dryers. This study aims to design and analyse the strength of a rotary dryer machine frame for maggot drying with a Finite Element Analysis (FEA) approach based on SolidWorks software. Simulations were carried out on several materials: ASTM A36, AISI 1020 Steel, and AISI 1045 Steel. The analysis results show that all materials are within safe limits based on Von Mises stress, deformation, and safety factor. AISI 1045 steel material gives the best performance with Von Mises stress of 14.238 MPa, deformation of 0.59 mm, and safety factor of 7.2. These results show that AISI 1045 steel is the most recommended material for the rotary dryer frame.